Tingkat Stres Kerja Perawat Instalasi Gawat Darurat pada Masa Pandemi Covid-19 - Dian Ika Puspitasari; Emdat Suprayitno; Bustami Bustami (Fakultas Ilmu Kesehatan, 2021)
Stress on nurses working in the emergency room, due to the Covid-19 pandemic which results in a higher risk of exposure, this happens because the nurses in the emergency room still don't know whether a patient is infected with a certain disease or not. The purpose of this study was to determine the level of stress on nurses working in the emergency department. This type of research is quantitative descriptive using a non-analytic cross-sectional design. The population in this study were nurses who worked in the emergency department as many as 22 people with total sampling. Based on the results of the study, it can be concluded that almost half of them are included in the very severe stress level, namely 8 people (36%),. It is hoped that all nurses, especially in the emergency unit room, will always comply with the Health protocol in preventing the transmission of Covid-19